Challenges in the teaching of speaking skills in Tamil subject among the Indian students at the National Primary school / Khasturi Ramalingam, Yeo Kee Jiar and Nur Ilianis Adnan - Ramalingam, Khasturi; Yeo, Kee Jiar; Adnan, Nur Ilianis (Universiti Teknologi MARA, Pulau Pinang, 2022)
Mastering all the four language skills has been the topmost priority among both first and second language learners all over the world. Apparently, speaking skills remain to be the most challenging among other skills in which many learners are still struggling to speak proficiently. Speaking is also considered as one of the most wanted language skills to acquire. There are many ways to improve speaking skills among primary school students. However, the emphasis of these speaking skills in Tamil language among National Primary school Indian students has been less prioritized by parents and students. In addressing the issue mentioned, this paper discusses the constraints in executing speaking skills in Tamil lessons from the aspects of teachers, students, school atmosphere and facilities. In addition, several recommendations and suggestions were proposed to overcome the aforesaid obstacles. This paper concludes that the teachers should be optimistic in embracing the changes and transformations taking place particularly in the effort of upholding the status of this subject to be of indispensable importance as other subjects in schools. Teachers also should determine the appropriate learning method, teaching materials, and instructional tools. It can be concluded that several recommendations and suggestions will improve speaking skills in Tamil among the Indian students at the National Primary school in Malaysia